Practice of key essential nutrition action messages and associated factors among mothers of children aged six months to two years old in Karat town, Konso zone, South Ethiopia, 2024: a community-based cross-sectional study - Kasse, Tsehaynew; Aschalew, Zeleke; Desalegn, Nathan; Jebero, Zenebe; Moga, Fikre; Haile, Addisalem (Frontiers in Public Health, 2024)
Background Key essential nutrition actions (ENA) messages are a comprehensive and evidence-based nutritional package designed to improve the nutritional status during the critical first 1,000 days of life. The poor practice of ENA contributes significantly to mortality and morbidity related to malnutrition in young children. However, there is a dearth of studies focusing on the practice of key ENA messages among mothers and the factors associated with their practice. Therefore, this study aimed to assess the practice of key ENA messages among mothers of children aged 6 months to 2 years in Karat town, Konso zone, South Ethiopia in 2024. Methods A community-based cross-sectional study involving 421 mothers of children aged 6 months to 2 years was conducted in Karat town, Konso zone, South Ethiopia from January 15 to February 29, 2024. Respondents were chosen using computer-generated random numbers. A structured, pretested, and interviewer-administered questionnaire was used to collect data. Following coding and entry into EpiData 3.1, the data were exported to SPSS version 25 for analysis. Logistic regression (bivariate and multivariable) was employed to identify factors influencing mothers’ practice of key ENA messages, and statistical significance was set at p < 0.05 with a 95% confidence interval. Results The study found that 47.6% (95% CI: 42.8, 52.42%) of mothers demonstrated good practices. Having secondary education or higher, institutional delivery, receiving nutritional counseling during antenatal care (ANC), receipt of postnatal care (PNC) services, having good knowledge, and having a good attitude towards ENA all increase the likelihood of good practice. Conclusion This study emphasizes the need for multifaceted interventions to improve ENA practice among mothers residing in Karat town. To effectively address this issue, it is crucial to implement targeted education programs, strengthen postnatal care services, and nutritional counseling into routine antenatal care, promote institutional deliveries, and enhance awareness.